Unmasking the Illusion of ESG Impact on Company Performance: Menguak Tabir Ilusi Dampak ESG terhadap Kinerja Perusahaan - Amanda, Dinny Drastistya; Hanif, Aisha (Indonesian Journal of Law and Economics Review, 2024)
General Background: Environmental, social, and governance (ESG) disclosures are increasingly recognized as critical components of corporate responsibility, yet their impact on financial performance remains contentious in the literature. Specific Background: In Indonesia, companies listed on the Indonesia Stock Exchange (IDX) are progressively adopting ESG frameworks, raising questions about the actual effects of such disclosures on their financial outcomes, specifically in terms of Price to Book Value (PBV). Knowledge Gap: While prior research emphasizes the importance of ESG factors, empirical studies demonstrating their impact on corporate performance, particularly within emerging markets like Indonesia, are limited and inconclusive. Aims: The study analyzes ESG Star Companies in Indonesia from 2017-2023, examining their impact on company performance through multiple linear regression analysis of annual and sustainability reports. Results: The findings reveal that ESG disclosures, including environmental, social, and governance factors, do not significantly affect company performance as measured by PBV. Novelty: This study contributes to the existing literature by providing empirical evidence from the Indonesian context, highlighting the paradox of strong ESG commitments with no corresponding financial performance benefits. Implications: ESG disclosures are crucial for corporate sustainability, but may not yield immediate financial gains, highlighting the need for companies to reassess their ESG strategies for increased accountability and investor value. Highlights: Minimal ESG impact on company performance via Price to Book Value. Focus on Indonesia fills knowledge gap in ESG research. Reevaluate strategies to enhance ESG value perception among stakeholders. Keywords: ESG disclosures, company performance, Indonesia Stock Exchange, Price to Book Value, corporate sustainability